Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Pd-functionalized carbon nanotubes for selective hydrogenation of 2-butyne-1,4-diol - Nadgeri, Jayprakash M.; Garade, Ajit C.; Tambe, Romana A.; Gokhale, Suresh P.; Rode, Chandrashekhar V. (Advanced Science Letters, 2010)
Multiwalled carbon nanotubes were prepared by thermal decomposition method followed by acid treatment and Pd-functionalization with PdCl2 by wet impregnation method. The Pd functionlized carbon nanotubes catalyst was characterized by BET, FT-IR, Raman, XRD, EDX, ICP-OES, SEM and TEM and was evaluated for its activity for hydrogenation of 2-butyne-1,4-diol. It showed higher selectivity (93%) to 2-butene-1,4-diol than Pd supported on commercial carbon (70% selectivity to 2-butene-1,4-diol) for complete conversion of 2-butyne-1,4-diol. The catalyst also exhibited excellent stability as evidenced by the three catalyst recycle experiments.

Control of competing hydrogenation of phenylhydroxylamine to aniline in a single-step hydrogenation of nitrobenzene to p-aminophenol - Nadgeri, Jayprakash M.; Biradar, Narayan S.; Patil, Priyanka B.; Jadkar, Sachin T.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2011)
Two steps involving catalytic hydrogenation of nitrobenzene to phenylhydroxylamine (PHA) in acid medium and its rearrangement to p-aminophenol (PAP) were studied separately in a batch reactor, using a well-characterized 3% Pt/C catalyst. The first step of hydrogenation of nitrobenzene to PHA could be carried out at 303 K and a H(2) pressure of 0.69 MPa with complete conversion of nitrobenzene, while the achieved selectivity to PHA was higher than 90% with some formation of aniline, even at lower temperature. The second step of PHA rearrangement to PAP could be achieved under a hydrogen atmosphere at elevated temperature of 353 K to give a maximum selectivity to PAP of 74%.

Selectivity tuning options in hydrogenation of m-chloronitrobenzene to m-chloroaniline over mono- and bimetallic supported Pt catalysts - Mane, Rasika B.; Potdar, Aparna S.; Nadgeri, Jayprakash M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
Supported monometallic (Pt, Ni,) and bimetallic (Ni-Pt) catalysts were prepared for the selective liquid phase hydrogenation of m-chlronitrobenzene to m-chloroaniline (m-CAN). It was found that the use of sodium carbonate as an additive substantially reduced the extent of dehydrohalogenation in the case of monometallic, 1% Pt/C catalyst, to give the highest selectivity of 96% to m-CAN. Ni-Pt bimetallic catalyst although showed almost complete selectivity (>99%) to m-chloroaniline; its activity was several fold lower than that of 1% Pt/C Na2CO3 system. However, compared with Ni monometallic catalyst, bimetallic Ni-Pt showed higher activity and selectivity due to the presence of electron rich surface metallic Pt stabilized by Ni having lower ionization potential compared with Pt.